Microbiological and Molecular Genetic Aspects of Antibiotic Resistance of Pseudomonas aeruginosa and Acinetobacter baumannii - Yu. E. Skurikhina; V. B. Turkutyukov (Эпидемиология и вакцинопрофилактика)
Relevance. The increase in the frequency of infections caused by Pseudomonas aeruginosa and Acinetobacter baumannii, which have a high level of resistance to many groups of antibiotics, requires a comprehensive study, including modern research methods.Aims. The study of regional features of the dynamics of the formation and circulation of antibiotic-resistant strains A. baumannii and P. aeruginosa.Materials and methods. During 2009-2018 we analyzed the data of microbiological laboratories of multidisciplinary hospitals and carried out a molecular genetic study of the determinants of antibiotic resistance by PCR of A. baumannii and P. aeruginosa strains isolated from clinical material in order to determine the level of variability of resistance.Results. The study revealed a tendency to increase in the proportion of strains A. baumannii and P. aeruginosa in the etiological structure of healh-care associated infections and purulent-septic infections; high incidence of strains resistant to cephalosporins, carbapenems, beta-lactams and multi-resistant strains. The appearance and distribution of the determinants of antibiotic resistance NDM-1 and MCR-1 in these bacteria were also detected.Conclusions. Over the past decade, a steady increase in the proportion of A. baumannii and P. Aeruginosa resistant to many antibiotics in patients in intensive care unit and surgery departments in hospitals of Vladivostok (Primorsky reg., Russia), and the emergence of new antimicrobial resistance mechanisms in these microorganisms.